2014
DOI: 10.1021/jp501541q
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Layers of β-Lactoglobulin and SDS at Air–Water Interfaces with Tunable Intermolecular Interactions

Abstract: Mixtures of β-lactoglobulin (BLG) and sodium dodecyl sulfate (SDS) were studied at pH 3.8 and 6.7 under equilibrium conditions. At these pH conditions, BLG carries either a positive or a negative net charge, respectively, which enables tunable electrostatic interactions between anionic SDS surfactants and BLG proteins. For pH 3.8, vibrational sum-frequency generation (SFG) and ellipsometry indicate strong BLG-SDS complex formation at air-water interfaces that is caused by attractive electrostatic interactions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 49 publications
3
31
0
Order By: Relevance
“…1a, and A2a show a progressive increase in the surface pressure with increasing concentration C SDS > 5 Â 10 À5 M (R S/P > 50) which is consistent with a continuous surface accumulation of SDS molecules and replacement of protein material from the surface [15,16,27,36]. In this C SDS range the competitive co-adsorption of free SDS and SDS/BLG complexes is well pronounced even in presence of higher protein concentrations, such as C BLG = 1.5 Â 10 À5 M (R S/P > 3.3) [42], C BLG = 5.45 Â 10 À5 M (R S/P > 0.9) [39] and C BLG P 7 Â 10 À4 M (R S/P > 0.07) [40]. Thus complexes with different degrees of increased hydrophilicity [41], respectively lower surface activity, are replaced by SDS.…”
Section: Simultaneous Adsorption Formation Of Complexes In the Bulksupporting
confidence: 71%
See 4 more Smart Citations
“…1a, and A2a show a progressive increase in the surface pressure with increasing concentration C SDS > 5 Â 10 À5 M (R S/P > 50) which is consistent with a continuous surface accumulation of SDS molecules and replacement of protein material from the surface [15,16,27,36]. In this C SDS range the competitive co-adsorption of free SDS and SDS/BLG complexes is well pronounced even in presence of higher protein concentrations, such as C BLG = 1.5 Â 10 À5 M (R S/P > 3.3) [42], C BLG = 5.45 Â 10 À5 M (R S/P > 0.9) [39] and C BLG P 7 Â 10 À4 M (R S/P > 0.07) [40]. Thus complexes with different degrees of increased hydrophilicity [41], respectively lower surface activity, are replaced by SDS.…”
Section: Simultaneous Adsorption Formation Of Complexes In the Bulksupporting
confidence: 71%
“…Binding studies revealed a dynamic equilibrium between complexes and free surfactant molecules in the bulk solution which has been estimated by measuring the concentration of the free surfactant molecules as a function of the binding ratio C S /C BLG , and for SDS/BLG complexes at pH 7 the maximum ratio was estimated to be about 1 in presence of 6 mM free surfactant molecules [40]. Note, that appearance of SDS molecules at the W/A surface of a mixed SDS/BLG solution at pH 6.7 has been detected by SFG spectroscopy for R S/P > 1.7, C SDS > 2.55 Â 10 À5 M at constant C BLG = 1.5 Â 10 À5 M [42]. The competitive adsorption of free surfactant molecules and complexes is evidenced by the fact that increasing R S/P in the range 1-50 leads to (i) a continuous decrease of the dilational modulus |E| as demonstrated by the data in Figs.…”
Section: Simultaneous Adsorption Formation Of Complexes In the Bulkmentioning
confidence: 87%
See 3 more Smart Citations